The dynamics of language : an introduction - Cann, Ronnie (Syntax and semantics ;, 2005)
For the whole of the last half-century, most theoretical syntacticians have assumed that knowledge of language is different from the tasks of speaking and understanding. There have been some dissenters, but, by and large, this view still holds sway. This book takes a different view: it continues the task set in hand by Kempson et al (2001) of arguing that the common-sense intuition is correct that knowledge of language consists in being able to use it in speaking and understanding."The Dynamics of Language" argues that interpretation is built up across as sequence of words relative to some context and that this is all that is needed to explain the structural properties of language. The dynamics of how interpretation is built up is the syntax of a language system. The authors' first task is to convey to a general linguistic audience with a minimum of formal apparatus, the substance of that formal system. Secondly, as linguists, they set themselves the task of applying the formal system to as broad an array of linguistic puzzles as possible, the languages analysed ranging from English to Japanese and Swahili.' This book makes an uncommon achievement in successfully using detailed analyses of typologically diverse languages to address foundational questions about what it means to know a language and about the relation between speaking and understanding. This book will be of interest to anybody who is serious about the cognitive science of syntax and semantics' - Colin Phillips, University of Maryland, USA. 'For anyone interested in the basic nature of natural language syntax, this book is a necessary, and enjoyable, read. The authors provide a new take on how interpretations are constructed by language users, and back up their general theoretical proposals with original analyses of an eclectic range of linguistic phenomena. The exposition is clear and engaging-and challenging. You will have some of your assumptions shaken up; whether they fall back in place, or are radically rearranged, the experience is stimulating' - Caroline Heycock, University of Edinburgh, UK.